Strategic directions of air space information control of air traffic - Харченко, В. П. (Proceedings of National Aviation University (archive), 1999)
Considered are the strategic directions of development of space information control systems of air traffic. Main attention is given to the global system of communication, navigation, observation and organization of air traffic